2018
DOI: 10.1111/jofo.12272
|View full text |Cite
|
Sign up to set email alerts
|

A review of threshold responses of birds to landscape changes across the world

Abstract: Identifying the threshold of habitat cover beyond which species of birds are locally lost is useful for understanding the biological consequences of landscape changes. However, there is little consensus regarding the impact of landscape changes on the likelihood of species extinctions. We conducted a literature search using Scopus and ISI Web of Knowledge databases to identify studies where bird species were used to estimate threshold responses to landscape changes. We obtained a list of 31 papers published fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 61 publications
(134 reference statements)
2
27
0
2
Order By: Relevance
“…Our result is consistent with a recent review on threshold responses of birds to habitat loss, which found a mean habitat cover threshold at 29.5% in tropical landscapes (Melo et al 2018). At low habitat levels, fragmentation effects compound those of habitat loss, such that the rate of change in the ecological response is greater than expected from habitat loss alone (Swift and Hannon 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result is consistent with a recent review on threshold responses of birds to habitat loss, which found a mean habitat cover threshold at 29.5% in tropical landscapes (Melo et al 2018). At low habitat levels, fragmentation effects compound those of habitat loss, such that the rate of change in the ecological response is greater than expected from habitat loss alone (Swift and Hannon 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Coextinction of phylogenetic related species may cause the loss of entire functional groups, since closely related species share a number of traits affecting particular functions of organisms, such as seed dispersal. With respect to our measure of habitat amount, we used the percentage of forest cover in a defined area, an important measure that is widely used in studies that investigate threshold responses to land cover change (Melo et al 2018). Although we recognize that spatial configuration and species traits may interact and affect thresholds (Villard and Metzger 2014), habitat cover plays a critical role in defining biodiversity persistence (Fahrig 2013, Banks-Leite et al 2014, Melo et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The biodiversity decline may be initiated if the amount of available habitat falls below a certain, often species-specific, threshold level 6 . This may lead to the emergence of non-linear response of biodiversity to habitat fragmentation 7 .…”
Section: Different Response Of the Taxonomic Phylogenetic And Functimentioning
confidence: 99%
“…Bird diversity can be constrained by ''thresholds'' of land-surface conditions-such as vegetation availability-in the wider landscape (Andersen et al 2009;Gutzwiller et al 2015). A global review of threshold responses to landscape-wide changes in LULC suggests that bird diversity is most affected if more than 27.9% of the landscape has changed (Melo et al 2018). With exception of a few BBS routes (Figs.…”
Section: Variability In Explanatory Power In Space and Functional Traitsmentioning
confidence: 99%